2021
DOI: 10.1016/j.jtocrr.2021.100181
|View full text |Cite
|
Sign up to set email alerts
|

Hookah Smoke Mediates Cancer-Associated Epigenomic and Transcriptomic Signatures in Human Respiratory Epithelial Cells

Abstract: Introduction: Although communal smoking of hookah by means of water pipes is perceived to be a safe alternative to cigarette smoking, the effects of hookah smoke in respiratory epithelia have not been well characterized. This study evaluated epigenomic and transcriptomic effects of hookah smoke relative to cigarette smoke in human respiratory epithelial cells.Methods: Primary normal human small airway epithelial cells from three donors and cdk4 and hTERT-immortalized small airway epithelial cells and human bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…To further examine this issue, we evaluated FILIP1L mRNA expression in more extensive NSCLC databases including paired tumor and NAT samples. Consistent with our previous report ( 13 ), FILIP1L mRNA expression was significantly decreased in both LUAD ( Fig. 1A ) and LUSC ( Supplementary Fig.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…To further examine this issue, we evaluated FILIP1L mRNA expression in more extensive NSCLC databases including paired tumor and NAT samples. Consistent with our previous report ( 13 ), FILIP1L mRNA expression was significantly decreased in both LUAD ( Fig. 1A ) and LUSC ( Supplementary Fig.…”
Section: Resultssupporting
confidence: 93%
“…We have shown that FILIP1L mRNA levels are lower in LUAD and LUSC compared with unpaired normal lung tissues ( 13 ). To further examine this issue, we evaluated FILIP1L mRNA expression in more extensive NSCLC databases including paired tumor and NAT samples.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Cigarette smoking is a wellknown risk factor for lung cancer [41], and carcinogens in cigarette smoke induce EREG upregulation in bronchial epithelial cells. The exposure of human bronchial epithelial cells to cigarette smoke extract upregulates EREG, which in turn promotes cell proliferation and protects against cigarette smoke-induced cytotoxicity [42,43]. The treatment of lung adenocarcinoma cells with benzo[a]pyrene, which is a potent carcinogen in cigarette smoke, increases EREG expression and promotes cell proliferation [44].…”
Section: Physiological Role Of Ereg In Human Airway Epithelial Cellsmentioning
confidence: 99%